Schoepfia Fruit Fly, Anastrepha interrupta Stone (Insecta: Diptera: Tephritidae) - Howard V. Weems; John B. Heppner (EDIS, 2012)
The schoepfia fruit fly is native to southern Florida. It is known only from coastal counties of south-central Florida to Key West, and only feeds on fruit of the flowering plant Schoepfia chrysophylloides. This revised 4-page fact sheet was written by H. V. Weems, Jr. and J. B. Heppner, and published by the UF Department of Entomology and Nematology, March 2012.